Characteristics of Diurnal Rainfall over Peatland Area of South Sumatra, Indonesia - Puad Maulana Mandailing; Wijaya Mardiansyah; Muhammad Irfan; Arsali Arsali; Iskhaq Iskandar (Science and Technology Indonesia, 2020)
The peak time of rainfall occurrence over an area has certain characteristics in which the difference in time and intensity of rainfall varies depending on its location and distance from the sea. This variation can be determined based on the phase and amplitude obtained using harmonic analysis. In this study, combined data from in-situ observation, satellite remote sensing and reanalysis were used to analyze spatial and temporal variations of peak rainfall events over peatland area of the South Sumatra Province. The results show that most of the South Sumatra Province has a diurnal peak of rainfall during afternoon ranging from 16.00 to 19.00 Western Indonesian Time. In addition, the results also indicate that the analysis on the in situ data revealed seasonal variation both in amplitude and time of maximum diurnal rainfall, while the reanalysis data only indicated a weak seasonal variation on the amplitude of the diurnal rainfall. Furthermore, spatial analysis shows that the time of maximum diurnal rainfall has spatial variation. Over the ocean, the time of maximum diurnal rainfall occurs during night time/early morning. Over the lowland or coastal area, the time of maximum diurnal rainfall occurs during afternoon, while over the high altitude (mountain) it occurs during late night.